2020
DOI: 10.1108/jocm-07-2020-0208
|View full text |Cite
|
Sign up to set email alerts
|

The dynamics of SME growth processes and the role of enabling constraints: an evidence-based theoretical framework

Abstract: PurposeThis paper aims to explain the dynamics of entrepreneurial decisions and actions (D&As) in the small and medium-sized enterprise (SME) growth process. The study focuses on the changing portfolio and relationship governance and captures these dynamics by using the concept of “enabling constraints” (ECs).Design/methodology/approachIn-depth, long-term and multiple-case study method was adopted based on six high-growth SMEs. Pattern-matching and alternative template approach formed a basis for developin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 101 publications
(220 reference statements)
0
3
0
Order By: Relevance
“…This research aims to contribute to the conceptual development of a special view of DL as a barrier to and enabler of innovation by explaining how DL is related to organizational transformation and to shaping managerial decision-making, especially under time pressure and causal ambiguity (March, 1991). This balanced view of DL ties in with most recent discourses on hybrid phenomena like 'enabling constraints' (Selden & Fletcher, 2015;Gancarczyk et al, 2021).…”
Section: Dominant Logic and Its Immanent Ambiguitymentioning
confidence: 98%
“…This research aims to contribute to the conceptual development of a special view of DL as a barrier to and enabler of innovation by explaining how DL is related to organizational transformation and to shaping managerial decision-making, especially under time pressure and causal ambiguity (March, 1991). This balanced view of DL ties in with most recent discourses on hybrid phenomena like 'enabling constraints' (Selden & Fletcher, 2015;Gancarczyk et al, 2021).…”
Section: Dominant Logic and Its Immanent Ambiguitymentioning
confidence: 98%
“…It is critical to study how company manages its growth process (Gupta, Guha & Krishnaswami, 2013), but the related research is scattered and only limited number of studies have the process approach (e.g. Davidsson & Wiklund, 2006;Gancarczyk, Freiling & Gancarczyk, 2021;Headd & Kirchhoff, 2009;Shim, Eastlick, & Lotz, 2000). There are numerous, general stages of growth models (see Levie & Lichtenstein, 2010;Phelps, Adams & Bessant, 2007), but only vague understanding on the context-specific characteristics such as in healthcare business.…”
Section: Key Concepts Of Growth Management Processesmentioning
confidence: 99%
“…This is in line with the pre-understanding that healthcare entrepreneurs are professionally oriented rather than business growth oriented: entrepreneurs' managerial focus is on care-taking their customers rather than on growth ambitions. The study of Delmar and Wiklund (2008) on small Swedish firms suggested an impact of motivation on employment growth, and a recent study by Gancarczyk et al (2021) pointed out that SME owner-managers' judgments about growth motives and rationales constrain their choices and how they enable new directions. In the present empirical data, the opposing roles of healthcare professional and entrepreneur (Numerato, Salvatore and Fattore, 2012;von Knorring, Alexanderson & Eliasson, 2014) were clearly apparent in most interviews, and it had impact on the managerial role the healthcare professional was willing to take as entrepreneur.…”
Section: [Insert Table 4 Here]mentioning
confidence: 99%